Existence of Positive Solutions of a Nonlinear Differential Equation with N Delays - Maria Kudelcikova (Communications - Scientific letters of the University of Zilina, 2014)
The equation yt abty t i t n 1 i x=+a = o^^ ^^ hhhh % is considered where n is a positive integer, a,τi and αi,i = 1,2,...,n are positive constants and conditions on function b are formulated such that the considered equation has positive solutions when t → ∞. The equation is studied under assumptions,.ae 11 ii i n i i n 11 1 ax a = == cm // Estimation of positive solutions is given as well. The proof is based on the retract technique.